Peran Kewirausahaan dalam Memaksimalkan Penjualan Barang Paling Laku di Tokoh Begi Shop - Karolus Wulla Rato; Theresia A.L Lemu; Densi Sovia Ngongo; Rinto Tonu Dama Gawang; Roberto Ambi Rato Gollu; Marianus Umbu (Institut Nalanda, 2025)
This study aims to examine the role of entrepreneurship in maximizing sales of best-selling items at Begi Shop. In an era of increasingly tight business competition, business owners need to implement effective entrepreneurial strategies to increase sales and competitiveness. This study identifies various entrepreneurial factors that influence sales, including marketing strategies, inventory management, product innovation, and customer service. In addition, this study also evaluates how technology, such as inventory management systems and data analytics, can support more informed decision-making in managing best-selling items. The research method used is a qualitative approach with a case study at Begi Shop, which involves interviews with business owners, managers, and customers. The results of the study indicate that entrepreneurship has a significant role in increasing sales of best-selling items through innovation in marketing, inventory management efficiency, and improved customer service. This study is expected to provide insight for other retail business owners to implement more effective entrepreneurial strategies in maximizing sales in a competitive market.